Detecting Patch Submission and Acceptance in OSS Projects - Bird, Christian (Proceedings of the Fourth International Workshop on Mining Software Repositories, 2016)
The success of open source software (OSS) is completely dependent on the work of volunteers who contribute their time and talents. The submission of patches is the major way that participants outside of the core group of developers make contributions. We argue that the process of patch submission and acceptance into the codebase is an important piece of the open source puzzle and that the use of patch-related data can be helpful in understanding how OSS projects work. We present our methods in identifying the submission and acceptance of patches and give results and evaluation in applying these methods to the Apache webserver, Python interpreter, Postgres SQL database, and (with limitations) MySQL database projects. In addition, we present valuable ways in which this data has been and can be used.